Progress in Community Nutrition - Bell, Colin; Love, Penelope (MDPI - Multidisciplinary Digital Publishing Institute, 2023)
Dietary patterns are evolving, and we are increasingly aware of the contribution of food and food systems to community and planetary health. To be responsive to these changes and to promote dietary patterns that enhance the health and wellbeing of populations and protect against climate change, nutrition professionals and researchers need to monitor evolving dietary patterns and trial comprehensive, multiaction solutions. Countries are pushing back on corporate and climate change disruptions to food systems and are looking for ways to strengthen community involvement in food systems, so that healthy and environmentally friendly food choices are easier to make. To achieve this, policymakers need access to the latest evidence on evolving dietary patterns and on effective solutions, and this Special Issue on Progress in Community Nutrition: Dietary Patterns and Planetary Health provides some of this evidence.